Airavat: Security and Privacy for MapReduce - Roy, Indrajit; Setty, Srinath; Kilzer, Ann; Shmatikov, Vitaly; Witchel, Emmett (Symposium on Networked Systems Design and Implementation (NSDI), 2010)
We present Airavat, a Map Reduce-based system which provides strong security and privacy guarantees for distributed computations on sensitive data. Airavat is a novel integration of mandatory access control and differential privacy. Data providers control the security policy for their sensitive data, including a mathematical bound on potential privacy violations. Users without security expertise can perform computations on the data, but Airavat conﬁnes these computations, preventing information leakage beyond the data provider’s policy. Our prototype implementation demonstrates the ﬂexibilityofAiravatonseveralcasestudies. The prototype is efﬁcient, with run times on Amazon’s cloud computing infrastructure within 32% of a MapReduce system with no security.